المشروعات الصغرى و المتوسطة في ظل العولمة التحديات و الفرص ( الحالة الليبية) (Al-Farooq Journal of Sciences, 2026)
This paper addresses the challenges facing small and medium-sized enterprises (SMEs) in Libya, particularly in light of international trade liberalization and increased global competition resulting from economic globalization. It highlights the experiences of other countries in this regard to draw lessons from them. The importance of this topic stems from the weak contribution of SMEs to the Libyan economy due to the obstacles and challenges they face, and the lack of attention given to them by the state, both in the past and present. This issue is further emphasized by the unique nature of the Libyan economy as a rentier economy. These enterprises represent a crucial tool for achieving economic growth and job creation, and can reduce dependence on oil and achieve economic diversification.